Hubungan Pembelajaran Akhlak dengan Perilaku Peserta Didik di Madrasah Ibtidaiyah Swasta Nurul Salam Lewoleba - Tasyrifany Akhmad (Lembaga Einstein College (LEC), 2024)
This research was conducted to discuss the implementation of moral learning, student behavior, and the relationship between moral learning and the behavior of class V students at the Nurul Salam Lewoleba Private Madrasah Ibtidaiyah. This type of research is descriptive and qualitative. Collection by means of observation, interviews, and documentation. The research subjects were moral aqidah teachers and class V students. The research instruments were written questions for which alternative answers had been prepared, then analyzed using deductive, inductive, and comparative thinking patterns. The results of this research illustrate that the level of understanding and development of moral learning at MIS Nurul Salam Lewoleba is categorized as good. The implementation of moral learning is basically to make students have Islamic behavior. Through the previous stages of implementing moral learning, the teacher prepares lesson plans, facilities, and media that will be used in conducting the learning, and the teacher strives to create an active and enjoyable learning atmosphere so that the behavior of class V students at the Nurul Salam Lewoleba Private Madrasah Ibtidaiyah becomes commendable. Creating commendable behavior among students creates a good learning atmosphere. Therefore, there is a positive and strong relationship between the level of understanding of the moral learning material and the social behavior of students at the Nurul Salam Lewoleba Private Madrasah Ibtidaiyah.